Prospects for HIV control in South Africa: a model-based analysis - Leigh F. Johnson; Calvin Chiu; Landon Myer; Mary-Ann Davies; Rob E. Dorrington; Linda-Gail Bekker; Andrew Boulle; Gesine Meyer-Rath (Global Health Action, 2016)
Background: The goal of virtual elimination of horizontal and mother-to-child HIV transmission in South Africa (SA) has been proposed, but there have been few systematic investigations of which interventions are likely to be most critical to reducing HIV incidence. Objective: This study aims to evaluate SA's potential to achieve virtual elimination targets and to identify which interventions will be most critical to achieving HIV incidence reductions. Design: A mathematical model was developed to simulate the population-level impact of different HIV interventions in SA. Probability distributions were specified to represent uncertainty around 32 epidemiological parameters that could be influenced by interventions, and correlation coefficients (r) were calculated to assess the sensitivity of the adult HIV incidence rates and mother-to-child transmission rates (2015–2035) to each epidemiological parameter. Results: HIV incidence in SA adults (ages 15–49) is expected to decline from 1.4% in 2011–2012 to 0.29% by 2035 (95% CI: 0.10–0.62%). The parameters most strongly correlated with future adult HIV incidence are the rate of viral suppression after initiating antiretroviral treatment (ART) (r=−0.56), the level of condom use in non-marital relationships (r=−0.40), the phase-in of intensified risk-reduction counselling for HIV-positive adults (r=0.29), the uptake of medical male circumcision (r=−0.24) and the phase-in of universal ART eligibility (r=0.22). The paediatric HIV parameters most strongly associated with mother-to-child transmission rates are the relative risk of transmission through breastfeeding when the mother is receiving ART (r=0.70) and the rate of ART initiation during pregnancy (r=−0.16). Conclusions: The virtual elimination target of a 0.1% incidence rate in adults will be difficult to achieve. Interventions that address the infectiousness of patients after ART initiation will be particularly critical to achieving long-term HIV incidence declines in South Africa.